Pretreatment method for reducing volatile matters in smelting process of porous titanium prepared by potassium fluotitanate aluminothermic method and application of pretreatment method

Through the pretreatment method of three-stage calcination and ultrasonic cleaning of tube furnace, the problems of skeleton collapse and impurity residues of porous titanium preparation during the smelting process are solved, and efficient volatile matter removal and material protection are achieved, and smelting efficiency and product quality are improved.

CN120460723APending Publication Date: 2025-08-12HARBIN INST OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510514112.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-23
Publication Date
2025-08-12

AI Technical Summary

Technical Problem

In the prior art, the preparation of porous titanium by potassium fluorotitanate aluminum thermal method has problems of skeleton structure collapse and residual C impurities during the smelting process, resulting in insufficient material density and metal loss, affecting the smelting efficiency and product quality.

Method used

The pretreatment method of three-stage calcination of tube furnace combined with water and acetone ultrasonic cleaning is adopted to remove volatile impurities through precise temperature control to avoid the introduction of impurities by mechanical stress and binder. The three-stage calcination is carried out under the protection of argon, and the insulation treatment is carried out at 600℃, 1000℃ and 800℃ respectively.

Benefits of technology

It effectively reduces the volatiles of porous titanium during hydrogen plasma arc smelting, maintains material density and structural integrity, reduces energy consumption, reduces environmental pollution, and recovers volatiles, improving smelting efficiency and product quality.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120460723A_ABST
    Figure CN120460723A_ABST
Patent Text Reader

Abstract

The invention discloses a pretreatment method for reducing volatile matters in a smelting process of porous titanium prepared by a potassium fluotitanate aluminothermic method and application of the pretreatment method. The invention belongs to the field of metal impurity removal and smelting. The problems that in the prior art, in order to solve the smelting problem of preparing the porous titanium through a potassium fluotitanate aluminothermic method, the porous titanium skeleton structure is irreversibly collapsed and the porosity is reduced due to the fact that the porous titanium is treated through mechanical pressing, and C impurities are left when the porous titanium is pretreated in a bonding forming mode are solved. According to the method for eliminating the volatile impurities by utilizing the tubular furnace, the impurities in the porous titanium can be removed in a targeted manner by utilizing three-section calcination treatment of the tubular furnace, K2TiF6 which is not completely reacted and residual Al can be further subjected to an aluminothermic reaction, the mass loss is further reduced in the hydrogen plasma arc melting process, the impurities are not introduced, and the method is suitable for industrial production. The pretreatment method disclosed by the invention can also be used for recovering volatile matters and greatly reducing environmental pollution, and has remarkable social benefits and economic benefits.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of metal impurity removal and smelting, and particularly relates to a pretreatment method for reducing volatiles in the smelting process of porous titanium prepared by a potassium fluorotitanate aluminothermic method and an application thereof. Background Art

[0002] As a key strategic material in modern industry, the application scope of titanium alloy has expanded from traditional aerospace (such as aircraft load-bearing structural parts and spacecraft fuel tanks) to emerging fields such as biomedicine (artificial joints and dental implants), marine engineering (pressure-resistant shells of deep-sea probes), and new energy (hydrogen energy storage and transportation equipment). However, the current mainstream preparation method for producing titanium alloys is the Kroll method, which has a complex process flow, high energy consumption, and low waste utilization rate. In the context of modern pursuit of environmental protection and energy conservation, the pressure on carbon emission reduction in the metallurgical industry continues to increase. Therefore, the development and improvement of short-process, low-cost titanium alloy preparation technology is of great practical significance.

[0003] The potassium fluorotitanate aluminothermic method for preparing porous titanium has low production costs, can effectively utilize by-products of the metallurgical process, and the raw materials are easily obtained. Potassium fluorotitanate can be directly prepared using HF, KOH, and H2TiO3 (an intermediate product of the sulfuric acid method for producing titanium dioxide) as raw materials. The preparation method is similar to the preparation method of cryolite (Na3AlF6) used in the aluminum electrolysis industry. It only needs to replace Al(OH)3 with H2TiO3. However, the porous titanium prepared by this process may have two problems on the production line due to the mixing and agglomeration reaction and distillation process in the process: first, the oxygen content of the material is higher than 2000ppm, which far exceeds the oxygen content standard of aviation-grade titanium materials (≤1500ppm); second, the porous structure leads to a low volume density. The porous titanium prepared by mixing and agglomerating has an irregular shape, uneven composition, and may even have incomplete reaction. Studies have shown that hydrogen plasma arc melting (HPAM) can reduce the oxygen content to below 800 ppm through the strong reducing effect of hydrogen, and the high temperature environment of HPAM can promote the continuation of unfinished reactions and the volatilization of impurities. However, in actual applications, it was found that the irregular shape of porous titanium leads to insufficient charging density (crucible filling rate <60%), and the volatile substances adsorbed in the pores during the melting process (mainly fluorides such as KF and AlF3) evaporate violently at high temperatures, which not only causes metal loss but also contaminates the melting equipment, seriously affecting the practical application of this technology.

[0004] In order to solve the problem of melting porous materials in the prior art, pretreatment methods such as mechanical pressing or bonding molding are mainly used, but these methods expose a series of problems in practical applications. First, although mechanical pressing can increase the bulk density of the material by applying high pressure, excessive compressive stress will cause the porous titanium skeleton structure to collapse irreversibly and the porosity to decrease, which may affect the subsequent infiltration deoxidation in the hydrogen plasma melting stage. Secondly, although the bonding molding technology can maintain a relatively high porosity, the commonly used organic binders such as polyvinyl alcohol (PVA) and polyacrylamide (PAM) will leave C impurities after high-temperature cracking, resulting in an increase in the carbon content of the titanium material after melting, which may reduce the fatigue strength of the material. In addition, the gaseous products such as CO and CH4 produced by the pyrolysis of some binders will react with the active titanium surface to form secondary inclusions such as TiC. The existing pretreatment process also has the defects of high energy consumption and low efficiency. These limitations seriously restrict the efficient utilization of porous titanium materials, so it is necessary to develop new pretreatment technologies to solve the problems of this production method. Summary of the Invention

[0005] The purpose of the present invention is to solve the problem of irreversible collapse of the porous titanium skeleton structure and reduced porosity in the prior art for the purpose of solving the smelting problem of porous titanium prepared by potassium fluotitanate aluminothermic method, and the problem of residual C impurities in the porous titanium pretreated by bonding molding. The present invention provides a pretreatment method for reducing volatiles in the smelting process of porous titanium prepared by potassium fluotitanate aluminothermic method and its application.

[0006] The technical solutions of the present invention are as follows:

[0007] One of the purposes of the present invention is to provide a pretreatment method for reducing volatiles in the smelting process of porous titanium prepared by potassium fluorotitanate aluminothermic method, wherein:

[0008] S1: Depending on the preparation process, the porous titanium prepared by potassium fluorotitanate aluminothermic method is in block or powder form. The block porous titanium needs to be processed into powder for the next experiment;

[0009] S2: Mix the porous titanium powder of S1 with deionized water, stir mechanically, and filter to retain the filter residue;

[0010] S3: ultrasonically clean the filter residue from S2 with distilled water, filter, and retain the solid powder;

[0011] S4: ultrasonically clean the solid powder obtained in S3 with acetone, filter, and then vacuum dry to obtain a pre-cleaned powder;

[0012] S5: The pre-cleaned powder obtained in S4 is placed in a tube furnace and subjected to three-stage calcination treatment, and then naturally cooled to room temperature.

[0013] It is further defined that the method for processing the bulk porous titanium in S1 is trimming or cutting and crushing, and the processed porous titanium must be screened through a sieve with a sieve diameter of ≤0.3 mm.

[0014] It is further defined that the diameter of the powdered porous titanium prepared by the potassium fluorotitanate aluminothermic method in S1 is ≤ 0.3 mm.

[0015] It is further defined that the volume ratio of the porous titanium powder of S2 to deionized water is 1:4-6, and the stirring time is 5-10 minutes.

[0016] It is further defined that the ultrasonic frequency in S3 is 40 to 60 kHz, and the ultrasonic time is 10 to 15 minutes.

[0017] It is further defined that the ultrasonic frequency in S4 is 40-60 kHz, the ultrasonic time is 10-15 min, the vacuum drying temperature is 60-80° C., and the drying time is 0.5-1 h.

[0018] It is further defined that the specific conditions of the three-stage calcination treatment in the S5 medium tubular furnace are: the first stage is heated to 600°C at 30°C / min, the second stage is heated to 1000°C at 20°C / min, and the third stage is cooled to 800°C. Argon is passed throughout the calcination and cooling process, and the argon flow rate is ≤100mL / min.

[0019] It is further defined that the first stage of the three-stage calcination in the S5 medium tubular furnace is kept warm for 10 to 20 minutes, the second stage is kept warm for 10 to 20 minutes, and the third stage is kept warm for 10 to 20 minutes.

[0020] A second object of the present invention is to provide a porous titanium powder prepared by the above-mentioned pretreatment method.

[0021] A third object of the present invention is to provide an application of the porous titanium powder in hydrogen plasma arc melting.

[0022] Compared with the prior art, the specific advantages of the present invention are as follows:

[0023] (1) The purpose of the present invention is to solve the problem of the prior art that the porous titanium skeleton structure is irreversibly collapsed and the porosity is reduced by mechanical pressing in order to solve the problem of smelting porous titanium by potassium fluotitanate aluminothermic method, and the problem that the porous titanium pretreatment method of bonding molding causes residual C impurities in the porous titanium. The present invention proposes a method for eliminating volatile impurities using a tubular furnace. The present invention first washes the sample with water and acetone to remove part of KAlF4 (slightly soluble in water) and other water-soluble impurities and organic impurities. Then, the sample is placed in a tube furnace for further treatment, and the whole process is carried out under argon protection. In the first stage, the sample is kept warm at 600°C for a period of time, and KAlF4 (melting point 500-600°C) and AlF3 (starting to sublime at about 500°C) are selectively removed. At the same time, the incompletely reacted K2TiF6 and residual Al can continue to undergo a thermite reaction. In the second stage, the sample is heated to 1000°C and kept warm, mainly to decompose the residual K3AlF6 and discharge gaseous fluoride (AlF3 generated by decomposition), while continuing the thermite reaction of the K2TiF6 that may not have reacted completely and the residual Al. In the third stage, the sample is kept warm at 800°C for a period of time to prevent incomplete removal of volatile impurities in the first two stages. Finally, the sample is cooled to room temperature in an argon atmosphere. This method achieves step-by-step removal of volatiles from titanium alloys produced by the potassium fluotitanate aluminothermic method through precise temperature control, eliminates impurities, and significantly reduces volatiles in the subsequent smelting process.

[0024] (2) The segmented insulation and dynamic temperature control technology of the present invention can effectively reduce the consumption of processing energy, and the pretreatment method of the present invention has no effect on the volume and density of the titanium material itself. The present invention does not change the volume density of porous titanium under mechanical stress conditions through ultrasonic cleaning with water and acetone and tubular furnace treatment, thereby avoiding the skeleton collapse caused by traditional pressing processes and ensuring the hydrogen penetration efficiency of subsequent hydrogen plasma smelting.

[0025] (3) The present invention adopts inorganic medium cleaning and argon protection treatment to eliminate carbon pollution introduced by the binder and oxygen pollution in the air, so the pretreatment method of the present invention will not introduce other impurities.

[0026] (4) The pretreatment method of the present invention can also recover volatiles. Most of the fluorides can be recovered through low-temperature condensation at the exhaust end of the tubular furnace and adsorption on molecular sieves, thereby significantly reducing environmental pollution. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 a is a physical picture of the TC4 porous titanium bulk sample in Example 1, Figure 1 b is a physical picture of the TiAl porous titanium block sample of Example 2;

[0028] Figure 2 This is the XRD detection pattern of volatiles of the TiAl porous titanium block sample that has not been pretreated in Example 2;

[0029] Figure 3 This is a photo of the TC4 porous titanium block sample that has not been pretreated in Example 1 after hydrogen plasma arc melting;

[0030] Figure 4 This is a photo of the TiAl porous titanium block sample that has not been pretreated in Example 2 after hydrogen plasma arc melting;

[0031] Figure 5 a is a photo of the porous titanium powder prepared in Example 1 after hydrogen plasma arc melting. Figure 5 b is a photo of the porous titanium powder prepared in Example 3 after hydrogen plasma arc melting;

[0032] Figure 6 a is a photo of the porous titanium powder prepared in Example 2 after hydrogen plasma arc melting. Figure 6 b is a photo of the porous titanium powder prepared in Example 4 after hydrogen plasma arc melting;

[0033] Figure 7 a is the XRD detection diagram of the TC4 porous titanium block sample without pretreatment in Example 1 after hydrogen plasma arc melting, Figure 7 b is the XRD pattern of the porous titanium powder prepared in Example 1 after hydrogen plasma arc melting;

[0034] Figure 8 a is the XRD test pattern of the TiAl porous titanium block sample without pretreatment after hydrogen plasma arc melting in Example 2, Figure 8 b is the XRD detection diagram of the porous titanium powder prepared in Example 2 after hydrogen plasma arc melting. DETAILED DESCRIPTION

[0035] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.

[0036] The experimental methods used in the following examples are conventional methods unless otherwise specified. The materials, reagents, methods, and instruments used are conventional in the art and can be obtained commercially by those skilled in the art unless otherwise specified.

[0037] As used in the following examples, the terms "comprising," "including," "having," "containing," or any other variations thereof, are intended to cover a non-exclusive inclusion. For example, a composition, process, method, article, or apparatus that comprises the listed elements is not necessarily limited to only those elements but may include other elements not expressly listed or inherent to such composition, process, method, article, or apparatus.

[0038] When amount, concentration or other value or parameter are represented with the range of scope, preferred range or a series of upper preferred value and lower preferred value limit, this should be understood as specifically disclosing all ranges formed by any pairing of any range upper limit or preferred value and any range lower limit or preferred value, and no matter whether this scope is disclosed separately.For example, when disclosing scope "1 to 5", described scope should be interpreted as including scope "1 to 4", "1 to 3", "1 to 2", "1 to 2 and 4 to 5", "1 to 3 and 5" etc.When numerical range is described in this article, unless otherwise stated, otherwise this scope is intended to include its end value and all integers and fractions within the scope.In this application specification and claims, range limitation can be combined and / or interchanged, and if these ranges are not otherwise stated, include all subranges contained therein.

[0039] The indefinite articles "a" and "an" before the elements or components of the present invention do not limit the quantity requirement (i.e. the number of times they appear). Therefore, "a" or "an" should be interpreted as including one or at least one, and elements or components in the singular also include plural forms, unless the quantity clearly refers to only the singular form.

[0040] The term "one embodiment" or "embodiment" of the present invention refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The phrase "in one embodiment" appearing in various places throughout this specification does not necessarily refer to the same embodiment, nor does it necessarily refer to a separate or selective embodiment that is mutually exclusive of other embodiments.

[0041] The endpoints of the ranges and any values disclosed in the present invention are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoints of each range, the endpoints of each range and individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, and these numerical ranges should be considered to be specifically disclosed herein.

[0042] This experiment used a tubular furnace with a tube size of 50 mm x 1000 mm and overall dimensions of 550 mm x 380 mm x 520 mm. Raw materials were sourced from Hebei Chengde Vanadium Titanium New Materials Co., Ltd. These materials included lump and powdered TC4 (85-90 wt% Ti, 4-6 wt% Al, 3-4 wt% V, 0.2-0.6 wt% K and other impurities) and lump and powdered TiAl (75-80 wt% Ti, 20-30 wt% Al, 0.2-0.6 wt% K and other impurities).

[0043] Example 1:

[0044] 200 g of TC4 porous titanium bulk sample prepared by potassium fluorotitanate aluminothermic method was taken and cut to powder. The porous titanium bulk sample was screened through a sieve with a diameter of ≤0.3 mm to obtain porous titanium powder. Deionized water with a volume five times that of the porous titanium powder was added and mixed evenly. After mechanical stirring for 5 minutes, the mixture was filtered and the filter residue was retained. The filter residue was ultrasonically cleaned with distilled water at an ultrasonic frequency of 40 kHz and an ultrasonic time of 10 minutes, and the solid powder was retained. The solid powder was ultrasonically cleaned with acetone and ultrasonically The frequency was 40 kHz, the ultrasonic time was 10 min, the powder was filtered, and then vacuum dried at 60 ° C for 1 h to obtain a pre-cleaned powder; the pre-cleaned powder was placed in a tubular furnace, argon was passed throughout the process, and the argon flow rate was 100 mL / min. Three-stage calcination treatment was carried out, the first stage was heated to 600 ° C at 30 ° C / min, and kept warm for 10 min, the second stage was heated to 1000 ° C at 20 ° C / min, and kept warm for 20 min, the third stage was cooled to 800 ° C, and kept warm for 10 min, and then naturally cooled to room temperature to obtain the treated porous titanium powder.

[0045] Example 2:

[0046] 200g of TiAl porous titanium block sample prepared by potassium fluorotitanate aluminothermic method was taken and cut to powder. The porous titanium block sample was screened through a sieve with a diameter of ≤0.3mm to obtain porous titanium powder. Deionized water with a volume five times that of the porous titanium powder was added and mixed evenly. After mechanical stirring for 5min, the mixture was filtered and the filter residue was retained. The filter residue was ultrasonically cleaned with distilled water at an ultrasonic frequency of 40kHz and an ultrasonic time of 10min, and the solid powder was retained. The solid powder was ultrasonically cleaned with acetone. The acoustic frequency is 40 kHz, the ultrasonic time is 10 min, filtered, and then vacuum dried at 60 ° C for 1 h to obtain a pre-cleaned powder; the pre-cleaned powder is placed in a tubular furnace, argon is passed throughout the process, and the argon flow rate is 100 mL / min. Three-stage calcination treatment is carried out, the first stage is heated to 600 ° C at 30 ° C / min, and kept warm for 10 min, the second stage is heated to 1000 ° C at 20 ° C / min, and kept warm for 20 min, the third stage is cooled to 800 ° C, kept warm for 10 min, and then naturally cooled to room temperature to obtain the treated porous titanium powder.

[0047] Example 3:

[0048] Take 200g of TC4 porous titanium powder sample prepared by potassium fluorotitanate aluminothermic method, add deionized water five times the volume of the porous titanium powder, mix evenly, mechanically stir for 5 minutes and then filter, retaining the filter residue; ultrasonically clean the filter residue with distilled water, ultrasonic frequency 40kHz, ultrasonic time 10min, filter, and retain solid powder; ultrasonically clean the solid powder with acetone, ultrasonic frequency 40kHz, ultrasonic time 10min, filter, and then vacuum dry at 60℃ for 0.5h to obtain pre-cleaned powder; place the pre-cleaned powder in a tubular furnace, pass argon throughout the process, argon flow rate 100mL / min, and perform three-stage calcination treatment, the first stage is heated to 600℃ at 30℃ / min, kept warm for 10min, the second stage is heated to 1000℃ at 20℃ / min, kept warm for 10min, the third stage is cooled to 800℃, kept warm for 10min, and then naturally cooled to room temperature to obtain the treated porous titanium powder.

[0049] Example 4:

[0050] Take 200g of TiAl porous titanium powder sample prepared by potassium fluorotitanate aluminothermic method, add deionized water five times the volume of the porous titanium powder, mix evenly, mechanically stir for 5 minutes and then filter, retaining the filter residue; ultrasonically clean the filter residue with distilled water, ultrasonic frequency 40kHz, ultrasonic time 10min, filter, and retain solid powder; ultrasonically clean the solid powder with acetone, ultrasonic frequency 40kHz, ultrasonic time 10min, filter, and then vacuum dry at 60℃ for 0.5h to obtain pre-cleaned powder; place the pre-cleaned powder in a tubular furnace, pass argon throughout the process, argon flow rate 100mL / min, and perform three-stage calcination treatment, the first stage is heated to 600℃ at 30℃ / min, kept warm for 10min, the second stage is heated to 1000℃ at 20℃ / min, kept warm for 10min, the third stage is cooled to 800℃, kept warm for 10min, and then naturally cooled to room temperature to obtain the treated porous titanium powder.

[0051] Comparative Example 1:

[0052] 200 g of TC4 porous titanium block sample prepared by potassium fluorotitanate aluminothermic method is taken and cut to process the porous titanium block sample into powder. The treated porous titanium is screened through a sieve with a sieve diameter of ≤0.3 mm to obtain porous titanium powder; deionized water five times the volume of the porous titanium powder is added, mixed evenly, mechanically stirred for 5 minutes and then filtered to retain the filter residue; the filter residue is ultrasonically cleaned with distilled water at an ultrasonic frequency of 40 kHz and an ultrasonic time of 10 minutes, filtered to retain the solid powder; the solid powder is ultrasonically cleaned with acetone at an ultrasonic frequency of 40 kHz and an ultrasonic time of 10 minutes, filtered, and then vacuum dried at 60°C for 1 hour to obtain a pre-cleaned powder; the pre-cleaned powder is placed in a tubular furnace, argon is passed throughout the process, the argon flow rate is 100 mL / min, and a single-stage constant temperature treatment is performed, the temperature is increased to 400°C at 30°C / min, kept warm for 30 minutes, and then naturally cooled to room temperature to obtain the treated porous titanium powder.

[0053] Comparative Example 2:

[0054] 200g of TiAl porous titanium bulk sample prepared by potassium fluorotitanate aluminothermic method was taken and cut to powder. The porous titanium bulk sample was screened through a sieve with a diameter of ≤0.3mm to obtain porous titanium powder. Deionized water with a volume five times that of the porous titanium powder was added and mixed evenly. After mechanical stirring for 5min, the mixture was filtered and the filter residue was retained. The filter residue was ultrasonically cleaned with distilled water at an ultrasonic frequency of 40kHz and an ultrasonic time of 10min, and the solid powder was retained. The powder was ultrasonically cleaned with acetone at a frequency of 40 kHz and a time of 10 min, filtered, and then vacuum dried at 60°C for 1 h to obtain a pre-cleaned powder. The pre-cleaned powder was placed in a tubular furnace, and argon was passed through the furnace at a flow rate of 100 mL / min. A two-stage calcination treatment was performed, with the first stage heating to 400°C at a rate of 30°C / min and holding for 15 min. The second stage heating to 650°C at a rate of 20°C / min and holding for 15 min was then naturally cooled to room temperature to obtain the treated porous titanium powder.

[0055] Mass loss test: The porous titanium powders prepared in Examples 1 to 4 and Comparative Examples 1 to 2 were ultrasonically cleaned with distilled water at an ultrasonic frequency of 40 kHz and an ultrasonic time of 10 min, filtered, and the solid powder was retained. The solid powder was then ultrasonically cleaned with acetone at an ultrasonic frequency of 40 kHz and an ultrasonic time of 10 min, and vacuum dried. 100 g of each was weighed and double-sided melted using hydrogen plasma arc melting (10 vol% H2, 90 vol% Ar) at a melting current of 300 A, single-sided melting for 5 min, and double-sided co-melting for 10 min. After the melting was completed, the powders were weighed again to calculate the mass loss. The results are shown in Table 1.

[0056] Table 1 Mass loss of porous titanium powders prepared in Examples 1 to 4 and Comparative Examples 1 to 2

[0057]

[0058] As can be seen from Table 1, the pretreatment method of the present invention can effectively reduce the mass loss of the porous titanium material during the hydrogen plasma arc melting process. It can be seen from Example 1, Example 2, Comparative Example 1 and Comparative Example 2 that the mass loss after the three-stage calcination treatment of the present application is also significantly lower than that of the single-stage calcination and the double-stage calcination. It can also be seen that although the weight of the powdered porous titanium material volatilized before and after pretreatment is more than that of the block porous titanium material, the corresponding volatile matter is also reduced a lot. The raw material Al content in the preparation process of TiAl porous titanium material is higher than that in the preparation process of TC4 porous titanium material, resulting in more AIF generated when preparing TiAl porous titanium material, so the TiAl porous titanium material has more volatile mass before and after pretreatment than the TC4 porous titanium material.

[0059] Figure 2 The XRD pattern of volatiles of TiAl porous titanium block sample without pretreatment in Example 2 is shown in Figure 2. Figure 2 We can see that the impurities contained in the TiAl porous titanium bulk sample that has not been pretreated in Example 2 are KAlF4, K3AlF6 and AI.

[0060] Figure 3 This is a photo of the hydrogen plasma arc melting of the TC4 porous titanium block sample that has not been pretreated in Example 1. Figure 3 It can be seen that the high-temperature volatilization of volatile substances during the smelting process causes an imbalance in the melt composition, resulting in the formation of pressure difference cavities at the solidification front, which makes it difficult for the ingot to be tightly formed, and eventually forms shrinkage cavities visible to the naked eye on the surface of the ingot. There may also be defects such as subcutaneous bubble groups or shrinkage.

[0061] Figure 4 This is a photo of the TiAl porous titanium block sample that has not been pretreated in Example 2 and has been melted by hydrogen plasma arc. Figure 4 It can be seen that the shape of the TiAl porous titanium block sample that has not been pretreated is irregular after hydrogen plasma arc melting. This is because the TiAl porous titanium block sample that has not been pretreated contains more impurities, and more volatiles are produced during the hydrogen plasma arc melting process, which affects the shape of the ingot.

[0062] Figure 5 a is a photo of the porous titanium powder prepared in Example 1 after hydrogen plasma arc melting. Figure 5 b is a photo of the porous titanium powder prepared in Example 3 after hydrogen plasma arc melting; Figure 6 a is a photo of the porous titanium powder prepared in Example 2 after hydrogen plasma arc melting. Figure 6 b is a photo of the porous titanium powder prepared in Example 4 after hydrogen plasma arc melting. Figure 5 a. Figure 5 b. Figure 6 a and Figure 6 As can be seen in b, the porous titanium powder prepared by the pretreatment method of the present invention has a complete and round ingot after hydrogen plasma arc melting, which proves that the present invention can effectively remove impurities in porous titanium and effectively reduce volatiles of porous titanium during hydrogen plasma arc melting.

[0063] Figure 7 a is the XRD detection diagram of the TC4 porous titanium block sample without pretreatment in Example 1 after hydrogen plasma arc melting, Figure 7 b is the XRD pattern of the porous titanium powder prepared in Example 1 after hydrogen plasma arc melting; Figure 8 a is the XRD test pattern of the TiAl porous titanium block sample without pretreatment after hydrogen plasma arc melting in Example 2, Figure 8 b is the XRD test pattern of the porous titanium powder prepared in Example 2 after hydrogen plasma arc melting. Figure 7 a. Figure 7 b. Figure 8 a and Figure 8 In b, it can be seen that the porous titanium powder prepared by the powder pretreatment method and the porous titanium powder pretreated by the present invention are smelted under (10 vol% H2, 90 vol% Ar), (20 vol% H2, 80 vol% Ar), (30 vol% H2, 70 vol% Ar) and pure Ar atmospheres. The XRD of the product obtained by melting under these conditions is compared with the XRD of the product before treatment. It can be seen that no phase change occurs before and after treatment, indicating that the pretreatment process of the present invention will not introduce other impurities and will not cause changes in the main phase composition and crystal structure. The phenomenon of inconsistent peak positions before and after smelting is because the smelting process causes changes in grain orientation, which reduces or even eliminates the diffraction intensity of certain crystal planes and increases the intensity of certain crystal planes.

[0064] The foregoing are merely preferred embodiments of the present invention. These embodiments are all different implementations based on the overall concept of the present invention. The scope of protection of the present invention is not limited thereto. Any changes or substitutions that can be easily conceived by a person skilled in the art within the technical scope disclosed in the present invention should be included within the scope of protection of the present invention. Therefore, the scope of protection of the present invention should be based on the scope of protection of the claims.

Claims

1. A pretreatment method for reducing volatiles in the smelting process of porous titanium prepared by potassium fluorotitanate aluminothermic method, characterized in that: The method: S1: Depending on the preparation process, the porous titanium prepared by potassium fluorotitanate aluminothermic method is in block or powder form. The block porous titanium needs to be processed into powder for the next experiment; S2: Mix the porous titanium powder of S1 with deionized water, stir mechanically, and filter to retain the filter residue; S3: ultrasonically clean the filter residue from S2 with distilled water, filter, and retain the solid powder; S4: ultrasonically clean the solid powder obtained in S3 with acetone, filter, and then vacuum dry to obtain a pre-cleaned powder; S5: The pre-cleaned powder obtained in S4 is placed in a tube furnace and subjected to three-stage calcination treatment, and then naturally cooled to room temperature.

2. The method according to claim 1, characterized in that The method for processing the bulk porous titanium in S1 is cutting or crushing, and the processed porous titanium is screened through a sieve with a diameter of 0.3 mm or less.

3. The method according to claim 1, characterized in that The diameter of the powdered porous titanium prepared by the potassium fluorotitanate aluminothermic method in S1 is ≤0.3 mm.

4. The method according to claim 1, wherein The volume ratio of the porous titanium powder of S2 to deionized water is 1:4-6, and the stirring time is 5-10 minutes.

5. The method according to claim 1, wherein The ultrasonic frequency in S3 is 40 to 60 kHz, and the ultrasonic time is 10 to 15 minutes.

6. The method according to claim 1, characterized in that In S4, the ultrasonic frequency is 40-60 kHz, the ultrasonic time is 10-15 min, the vacuum drying temperature is 60-80° C., and the drying time is 0.5-1 h.

7. The method according to claim 1, characterized in that The specific conditions of the three-stage calcination treatment in the S5 medium tube furnace are as follows: the first stage is heated to 600°C at 30°C / min, the second stage is heated to 1000°C at 20°C / min, and the third stage is cooled to 800°C. Argon is passed throughout the calcination and cooling process, and the argon flow rate is ≤100mL / min.

8. The method according to claim 1 or 7, characterized in that The first stage of the three-stage calcination in the S5 medium tube furnace is kept warm for 10 to 20 minutes, the second stage is kept warm for 10 to 20 minutes, and the third stage is kept warm for 10 to 20 minutes.

9. A porous titanium powder, characterized in that The porous titanium powder is prepared by the preparation method according to any one of claims 1 to 8.

10. Use of the porous titanium powder according to claim 9 in hydrogen plasma arc melting.